2022
DOI: 10.1097/md.0000000000028722
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 (COVID-19) pneumonia patient treated with two doses of infliximab within 2 weeks for acute severe ulcerative colitis

Abstract: Rationale: The ongoing coronavirus pandemic has caused severe acute respiratory syndrome, posing a significant challenge for patients receiving immunotherapy for immune-mediated inflammatory diseases. As of January 2022, immunosuppressants such as tumor necrosis factor inhibitors (anti-TNFα) and azathioprine are inadvisable for an infectious disease caused by the SARS-CoV-2 virus (COVID-19). We continued infliximab as a second induction dose nine days after the onset of COVID-19 symptoms in a pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Taken together, these data strongly support the clinical course that anti-TNFα agents do not worsen the COVID-19 infection. Alhalabi et al reported a case of a UC patient with COVID-19 pneumonia who was safely treated with an anti-TNFα agent [ 25 ]. However, data remain limited on the efficacy and the safety of anti-TNFα treatment in patients with COVID-19, based on large-scale clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data strongly support the clinical course that anti-TNFα agents do not worsen the COVID-19 infection. Alhalabi et al reported a case of a UC patient with COVID-19 pneumonia who was safely treated with an anti-TNFα agent [ 25 ]. However, data remain limited on the efficacy and the safety of anti-TNFα treatment in patients with COVID-19, based on large-scale clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…73 Additionally, clinicians observed higher levels of pro-inflammatory cytokines, namely TNF-a and IL-6, are present in concomitant IBD and COVID-19 than in either entity alone. 73 Follow-up studies from both Bezzio et al 74 and Alhalabi et al 75 have demonstrated the safety and efficacy of infliximab induction in patients with ASUC and acute COVID-19 pneumonia. In the former study, researchers appreciated a resolution of pulmonary symptoms in addition to IBD remission after treatment with anti-TNF therapy.…”
Section: Medical Managementmentioning
confidence: 99%
“…As a matter of fact, anti-TNF agents have an important anti-inflammatory effect and the ability to reduce the expression of some cytokines associated with poor outcomes in COVID-19 pneumonia [ 23 ]. As far as we know, there are no RCTs on the use of anti-TNF in severe COVID-19, and our knowledge derives from indirect observations of patients who are on anti-TNF drugs for underlying comorbidities and who contract SARS-CoV-2 infection; observational studies suggest that those patients tend to have a better outcome [ 59 , 60 ]. Therapy with anti-TNF antibody infliximab, however, is considered a major risk factor for IPA infection, with an even higher incidence described when the patient is in concomitant chronic steroid treatment [ 61 ].…”
Section: Impact Of Covid-19 Therapy On Capamentioning
confidence: 99%